(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
Integrated reports represent an episode in the development of the financial reporting function and were approved by the management of economic units as a result of the pressures of users of accounting information in light of a competitive economic environment that requires reducing the information gap between management and users in order to ensure the achievement of social and environmental activities to evaluate the efforts of the management of economic units and their ability to achieve goals. Its strategy and creating an integrated information advantage. The importance of the research stems from the importance of integrated reports and evaluation of banking performance and governance, as it addresses an important issue supporting the disclosure of quantitative and qualitative information about the performance of banks to meet the needs of investors and stakeholders. The aim of the research was to determine the role of the dimensions of integrated reports within the governance framework in the process of results and evaluation of banking performance. As for the research problem, the process of reporting on the results of the economic unit’s work is accompanied by various problems that prompted the emergence of a comprehensive type of reports. Hence, the research problem can be formulated with the following questions: Do the contents of the dimensions of integrated reports affect the evaluation of banking performance within the framework of governance? The research is also based on the following hypotheses: The first main hypothesis: There is a role for integrated reports with their dimensions within the governance framework in evaluating banking performance under the Balanced Scorecard (BSC) system. Many conclusions were reached: weak disclosure in the non-financial reports of the bank in the research sample, in addition to the low levels of environmental and social activities that help management achieve its set goals, and the low utility of the information provided to users. The research summarized the recommendations, the most important of which are the need to oblige professional accounting organizations and the management of the Iraqi Stock Exchange to direct bank management and the need to commit to preparing annual integrated reports.